Horizontal Transfer of phnAc Dioxygenase Genes within One of Two Phenotypically and Genotypically Distinctive Naphthalene-Degrading Guilds from Adjacent Soil Environments - Wilson, Mark S. (American Society for Microbiology, 2003)
Several distinct naphthalene dioxygenases have been characterized to date, which provides the opportunity to investigate the ecological significance, relative distribution, and transmission modes of the different analogs. In this study, we showed that a group of naphthalene-degrading isolates from a polycyclic aromatic hydrocarbon (PAH)-contaminated hillside soil were phenotypically and genotypically distinct from naphthalene-degrading organisms isolated from adjacent, more highly contaminated seep sediments. Mineralization of (14)C-labeled naphthalene by soil slurries suggested that the in situ seep community was more acclimated to PAHs than was the in situ hillside community. phnAc-like genes were present in diverse naphthalene-degrading isolates cultured from the hillside soil, while nahAc-like genes were found only among isolates cultured from the seep sediments. The presence of a highly conserved nahAc allele among gram-negative isolates from the coal tar-contaminated seep area provided evidence for in situ horizontal gene transfer and was reported previously (J. B. Herrick, K. G. Stuart-Keil, W. C. Ghiorse, and E. L. Madsen, Appl. Environ. Microbiol. 63:2330-2337, 1997). Natural horizontal transfer of the phnAc sequence was also suggested by a comparison of the phnAc and 16S ribosomal DNA sequences of the hillside isolates. Analysis of metabolites produced by cell suspensions and patterns of amplicons produced by PCR analysis suggested both genetic and metabolic diversity among the naphthalene-degrading isolates of the contaminated hillside. These results provide new insights into the distribution, diversity, and transfer of phnAc alleles and increase our understanding of the acclimation of microbial communities to pollutants.